MODELLING FOR SOIL EROSION AND RIVER SUSPENDED SEDIMENT - ABD HALIM, MUHAMMAD HAZIQ HAZIM (Universiti Teknologi PETRONAS, 2020)
Soil erosion and river suspended sediment are key to environmental problems in a certain places or region. These two problems can lead to many serious problems which affected the nature and life ecosystem. Some of the major problems caused by soil erosion and river suspended sediment are destroyed of marine life due to the polluted water, flooding that caused by erosion of soil which shallow the river, lower in land productivity as loss of the fertile soil and etc. The soil erosion and sediment transport in river are strongly affected by climate and land uses changes. A study on how for soil erosion and river suspended sediment have been conducted to counter and reduce the problems from keep going to be one of the major concern to environment and ecosystem. There were many types of models can be used for modeling soil erosion and sediment transport in river but each model have its advantages and disadvantages to be used.